A Novel Four-Terminal Ferroelectric Tunnel FET for Quasi-Ideal Switch - Kumar M.; Jit S. (My University, 2025)
This letter reports a novel four-terminal ferroelectric tunnel field effect transistor (4T Fe-TFET) on SOI substrates where an extra tunnel-gate (T-Gate) isolated from the main drive gate has been placed over the source region of Fe-TFET to achieve the steepest possible subthreshold swing (SS) characteristics below the Boltzmann limit. The tunneling length of the Fe-TFET is observed to be decreased with the increase in the negative bias voltage of the T-gate which has been explored for improving the SS as low as 0.5 mV/dec for sub-30 nm channel length Fe-TFETs and thereby making the proposed 4 T Fe-TFET a wonderful quasi-ideal CMOS switching device. © 2015 IEEE.